Seventy years of evidence on the efficacy and safety of drugs for treating leprosy: a network meta-analysis. Issue 4 (April 2023) - Yang, Jiaru; Kong, Jing; Li, Bingxue; Ji, Zhenhua; Liu, Aihua; Chen, Jingjing; Liu, Meixiao; Fan, Yuxin; Peng, Li; Song, Jieqin; Wu, Xinya; Gao, Li; et al.
Summary: Objective: The World Health Organization (WHO) recommends multidrug therapy (MDT) with rifampicin, dapsone, and clofazimine for treating leprosy, which is based on very low-quality evidence. Here, we performed a network meta-analysis (NMA) to produce quantitative evidence to strengthen current WHO recommendations. Method: All studies were obtained from Embase and PubMed from the date of establishment to October 9, 2021. Data were synthesized with frequentist random-effects network meta-analyses. Outcomes were assessed using odds ratios (ORs), 95% confidence intervals (95% CIs), and P score. Results: Sixty controlled clinical trials and 9256 patients were included. MDT was effective (range of OR: 1.06–1255584.25) for treating leprosy and multibacillary leprosy. Six treatments (Range of OR: 1.199–4.50) were more effective than MDT. Clofazimine (P score=0.9141) and dapsone+rifampicin (P score=0.8785) were effective for treating type 2 leprosy reaction. There were no significant differences in the safety of any of the tested drug regimens. Conclusions: The WHO MDT is effective for treating leprosy and multibacillary leprosy, but it may not be effective enough. Pefloxacin and ofloxacin may be good adjunct drugs for increasing MDT efficacy. Clofazimine and dapsone+rifampicin can be used in the treatment of a type 2 leprosy reaction. Single-drug regimens are not efficient enough to treat leprosy, multibacillary leprosy, or a type 2 leprosy reaction. Availability of data and materials: All data generated or analyzed during this study are included in this published article [and its supplementary information files]. Highlights: WHO multidrug therapy (MDT) is still the mainstay for leprosy treatment. Pefloxacin, ofloxacin, acedapsone, and prednisolone may augment efficacy of MDT. Most single-drug regimens were less effective than multidrug regimens. Difference of safety has not been observed among drugs for treating leprosy.